A 2D/3D g-C3N4/ZnO heterojunction enhanced visible-light driven photocatalytic activity for sulfonamides degradation. Issue 5 (1st March 2022) - Sun, Qi; Sun, Ying; Zhou, Miya; Cheng, Huanmei; Chen, Haoyu; Dorus, Brian; Lu, Man; Le, Tao
Abstract: To date, developing an efficient and economical method for the removal of sulfonamides is essential but yet challenging. This paper proposes a facile method to synthesize an efficient photocatalytic material denoted as CNZn heterojunction through in situ surface modification of g-C3 N4 on ZnO nanoparticles. The as-obtained photocatalyst of CNZn has a three-dimensional (3D) spherical ZnO nanoparticles architecture wrapped on two-dimensional (2D) g-C3 N4 nanosheets. Furthermore, other physicochemical properties of the novel photocatalyst were also analyzed in detail using X-ray diffraction, photoluminescence emission spectra, and UV–vis diffuses reflectance. The effects of catalyst dosage and solution pH on sulfamethoxazole (SMZ) degradation efficiency was also investigated. The optimized CNZn heterojunction exhibited 1.61-fold and 2.23-fold higher degradation efficiency for SMZ when compared to g-C3 N4 and ZnO alone under the same experimental conditions. Compared with sulfafurazole (SFZ) and sulfadimidine (SDD), we found that SMZ was more easily photodegradated under visible-light irradiation (λ > 400 nm) due to the different molecular structure. The results of the trapping experiments revealed that both holes and superoxide radicals are the main active substances involved in the mechanism of SMZ photodegradation. Furthermore, the possible enhanced photocatalytic mechanism for SMZ degradation by the use of a CNZn heterojunction photocatalyst is proposed in this study. The results of this study provide an excellent reference for the construction of high-performance photocatalysts in the future.